Draft Annual Plan 1978-79 Government of Andhra Pradesh - Planning Commission (Planning Commission, 1978)
For the year 1977-78, the Planning Commission approved a Plan of Rs 365.75 crores. In the vote on Account budget, the outlay on the Annual Plan for 1977-78 was Rs 365.75 crores compared to Rs 290.38 crores in 1976-77. This outlay has further been stepped up to Rs 380.38 crores so as to increase the allocation for the core sectors of Power end Irrigation on the one hand and for programmes for the Weaker Sections on the other.
Government of Andhra Pradesh, Finance and Planning (Planning Wing-IV) Department